Rancang Bangun Robot Pemungut dan Pelontar Bola sebagai Sarana Pendukung Pelatihan Atlet Penjaga Gawang Permainan Futsal - Akhmad Rizal Dzikrillah; Ahmad Ahdani; Qolibu Rozak Al-Tain; Muhammad Faishal (Prosiding Seminar Nasional Teknoka, 2024)
Goalkeepers need to practice their abilities in protecting the goal. Coaches often use ball throwing machines to train goalkeepers because the machine's throwing power tends to be stable and more controllable than humans. The current ball throwing machine still requires human assistance to pick up the ball from the floor, making the machine still very dependent on humans in picking up the ball. This research aims to design a ball throwing machine that has the additional capability of being able to pick up the ball from the floor and then throw it into the goal. By using rotating rubber cylinders, futsal balls that are on the ground can be picked up by the machine and then pushed to the throwing wheel. The torque and high rpm motor on the throwing wheel is capable of throwing the ball up to a distance of 4 meters. By using a combination of 4 omni wheels, a ball throwing machine can be built that is capable of moving with 3 degrees of freedom, namely forward-backward, turning right-left, and sliding right-left.